تخطيط و تصميم مدينة ترقوميا الصناعية - عمرو, اسيل; قباجة, ميس; نمر, نداء (جامعة بوليتكنك فلسطين - كلية الهندسة - معماري, 2017)
تهدف هذه الدراسة إلى تحليل الواقع الصناعي في فلسطين، و في محافظة الخليل على وجه الخصوص، وتوزيع المنشآت الصناعية فيها، وتحديد المعايير التخطيطية والتصميمية للمدن الصناعية من أجل إنشاء مدينة صناعية على مستوى المحافظة تقع على أراضي بلدتي ترقوميا وبيت أوال بالقرب من معبر ترقوميا. و تحاول الدراسة اإلجابة على مشكلة البحث والتي توضح توزيع المنشآت الصناعية في محافظة الخليل بشكل عشوائي وغير منظم، لعدة أسباب منها إستيالء اإلحتالل الصهيوني على أراضي محافظة الخليل وخاصة على األراضي الحدودية للمحافظة، مما يعيق إقامة المصانع على أطراف المحافظة، ويضطر المستثمر ون إلى إقامة مصانعهم في وسط المناطق السكنية مما يؤدي إلى الخلط في إستخدامات األراضي، هذا باإلضافة الى ما يعانيه أصحاب المصانع من نقص في خدمات البينة التحتية . وأظهرت الدراسة عدة نتائج منها دور القطاع الصناعي المهم في دعم القطاع اإلقتصادي للدولة، فوجب عليها اإلهتمام بالقوانين اإلقتصادية والتجارية المحفزة لإلستثمار، و يتعدى دور المدن الصناعية من كونها تمثل دعم لعملية النمو اإلقتصادي إلى تحقيق فوائد تعود على المناطق الحضرية والريفية من حيث تخصيص األراضي لإلستعمال الصناعي ورفع كفاءة إستخدام األرض، وكما أن نجاح المدينة الصناعية يعتمد على الموقع اإلستراتيجي لها من حيث قربها من المعابر والمناطق الحدودية، و مدى تقديم التسهيالت واإلعفاءات للمستثمرين فيها، و تحقيق العزل المناسب والكافي والتخفيف من الضوضاء والتلوث الناتج عنها. والتخطيط والتصميم الجيد لجميع مكوناتها ومرافقها . وتوصي الدراسة بنقل كافة الصناعات خارج حدود التجمعات السكنية لما لها من أضرار بيئية وصحية على المجتمع، و الحرص على توفير العزل المناسب بين المناطق الصناعية وجوارها من خالل األحزمة الخضراء، و العمل على التدرج في توزيع الصناعات حسب تأثيرها البيئي من خالل تجميع الصناعات المتشابهة للتحكم في إنبعاثاتها وتسهيل تجميع ومعالجة المخلفات داخل المجموعة الواحدة . The purpose of this study is to analyze the industrial reality in Palestine, in Hebron particular, and the distribution of industrial establishments therein, and to define the planning and design criteria for industrial cities in order to establish an industrial city which is located in Tarqumiya and Beit Ola lands . The study also attempts to answer the problem of searching and illustrating the distribution of industrial establishments in Hebron at random and disorganised, and due to several reasons including the takeover of the Zionist occupation in the territory of Hebron, especially on the border territories of the province, hampering establishment of factories on the outskirts of Province, and forced investors to set up factories in Central residential areas leading to confusion in land uses, in addition to what the manufacturers of deficiency in infrastructure services . The study showed several results, including the role of the industrial sector in supporting the economic sector of the country, so It must pay attention to economic and trade laws that stimulate investment , The role of industrial cities goes beyond supporting the process of economic growth to the benefits of urban and rural areas in terms of allocating land for industrial use and raising the efficiency of land use , The success of the industrial city depends on its strategic location in terms of proximity to the crossings and border areas, and the extent of providing facilities and exemptions to investors, and achieve adequate isolation and adequate and reduce the noise and pollution resulting from it. Planning and good design for all its components and facilities. The study recommends moving all industries outside the boundaries of residential communities because of their environmental and health damage to the community, and ensure appropriate segregation between industrial areas and its vicinity through green belts, and work on the gradual distribution of industries according to their environmental impact by grouping industries Similar to control emissions and facilitate gathering and processing residues inside the group .
CD, no of pages 167, معماري 16/2017 , in the store
Keywords: ترقوميا, الصناعيه,تخطيط